Classroom Push and Pull Factors’ Influence on Value Addition in Secondary Education in Public Secondary Schools in Rachuonyo South Sub-County, Kenya - Odera, Phelix; Sika, James; Olel, Maureen (African Journal of Education and Practice, 2025)
Purpose: The study sought to examine classroom push and factors’ influence on value addition in secondary educations of 2013 and 2014 cohorts in public secondary schools in Rachuonyo South Sub- County. Methodology: The study adopted correlational research design to measure and describe the degree of association between independent and dependent variable data sets. The populations for the study were 44 public secondary schools and 4351 students. Yamane’s formula was used to determine 39 public secondary schools from where 10 students were simple randomly sampled from each candidate class to represent a cohort apiece. The total sample of students in the study was 780. Data were collected using a researcher modified What Is Happening In Classroom Questionnaire (WIHICQ). Data analysis was done using descriptive statistics (frequencies, means) and inferential statistics (simple linear regression analysis) with the aid of Statistical Package for Social Sciences (SPSS) V.25 software. Findings: Regression analysis revealed that classroom push and pull factors account for up to 16% change in value addition in secondary education of the 2013 cohort and that classroom push and pull factors (P≤.05; β=0.386) have a weak significant positive relationship with value addition in secondary education of 2013 cohort. For the 2014 cohort, regression analysis revealed that classroom push and pull factors account for 10% change in value addition in secondary education and that classroom push and pull factors (P≤.05; β=0.358) have a weak significant positive relationship with value addition in secondary education. Unique contribution to Theory, Practice and Policy: The study examines the relationship between classroom push and pull factors and value addition in secondary education in Kenya based on Bowlby’s (1969) Attachment Theory. The analysis highlights how classroom relationships among students and teachers shape students’ academic progress in Kenya while providing insights that may inform research in comparable to other countries’ contexts.